Defects in antigen-driven lymphocyte responses in common variable immunodeficiency (CVID) are due to a reduction in the number of antigen-specific CD4+ T cells. - Funauchi, M (1995)
T cells from patients with CVID have defects that may relate to the failure in vivo of B cell production of antibodies. Antigen-driven responses of T cells from CVID patients and normal subjects have been assessed by measuring DNA synthesis in vitro. Low density cells enriched for antigen-presenting dendritic cells were pulsed with purified protein derivative (PPD) and cultured with autologous T cells. Overall, T cells from CVID patients showed a significantly low mean response to PPD, although non-specific DNA synthesis induced in CVID T cells by IL-2 was within the normal range. However, mean PPD-specific T cell responses in CVID were not restored by IL-2 irrespective of the presence of monocytes. Depletion of CD8+ cells also failed to restore the mean PPD response of CVID CD4+ T cells. Limiting dilution analysis showed that in CVID there was a reduced frequency of antigen-specific cells within the T cell preparations. The mean frequency of the PPD-specific T cells in cultures from patients vaccinated with bacille Calmette-Guérin (BCG) was reduced to 1 in 109,000 T cells compared with 1 in 18,600 T cells in BCG-vaccinated normal donors. These data show that the reduced PPD-specific response in CVID is due to a partial peripheral loss of antigen-specific cells.